1997
DOI: 10.1002/clc.4960200116
|View full text |Cite
|
Sign up to set email alerts
|

Paracardiac masses caused by a right coronary artery aneurysm and a saphenous vein graft aneurysm

Abstract: Summary: Two unusual cases of large aneurysms, one located in the native right coronary artery and the other in a saphenous vein graft, are reported. Their size and mode of presentation as asymptomatic paracardiac masses on chest x-ray films make them unique. It is proposed that these entities be considered as part of the differential diagnosis of paracardiac masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Since the first SVG aneurysm was reported in 1975, there have been almost 50 published cases. These aneurysms ranged from 1–14 cm 10 in diameter. The reported interval between CABG and diagnosis of the aneurysm is from a few days to 20 years 2 .…”
mentioning
confidence: 99%
“…The reported interval between CABG and diagnosis of the aneurysm is from a few days to 20 years 2 . Although there is no universal definition in the literature regarding what is considered an aneurysm, the most widely accepted definition is a dilatation of more than 1.5 times the diameter of the adjacent normal segment 10 …”
mentioning
confidence: 99%